Berlayar di Tengah Badai - Garadian, Endi Aulia (Masyarakat Sejarawan Indonesia, 2020)
This article discusses climate change in the Malacca Strait, both recorded in official government records and the Malay literary tradition. The sea that connects the Pacific Ocean to the Indies are indeed often experiencing the conjuncture, a situation where the weather can change suddenly. This natural phenomenon in turn makes all shipping and voyage activities in the Straits of Malacca, which is actually not quite large in scope, full of risk. In the report, the meteorological record and the strands of imagination in Malay literary works, at least, it seems that navigating the strait is not as easy as imagined, especially in the 1850-1885, years where shipping technology and climatology were not as sophisticated as this. The study also shows how sunspots affect changes in weather in the Malacca Strait.